The Role of Medical Imaging in the Recharacterization of Mild Traumatic Brain Injury Using Youth Sports as a Laboratory - Talavage, Thomas M.; Nauman, Eric A.; Leverenz, Larry J. (Frontiers in Neurology, 2016)
The short- and long-term impact of mild traumatic brain injury is an increasingly vital concern for both military and civilian personnel. Such injuries produce significant social and financial burdens, and necessitate improved diagnostic and treatment methods. Recent integration of neuroimaging and biomechanical studies in youth collision-sport athletes has revealed that significant alterations in brain structure and function occur even in the absence of traditional clinical markers of "concussion". While task performance is maintained, athletes exposed to repetitive head accelerations exhibit structural changes to the underlying white matter, altered glial cell metabolism, aberrant vascular response and marked changes in functional network behavior. Moreover, these changes accumulate with accrued years of exposure, suggesting a cumulative trauma mechanism that may culminate in categorization as "concussion" and long-term neurological deficits. The goal of this review is to elucidate the role of medical imaging in re-characterizing traumatic brain injury, as a whole, to better identify at-risk individuals and improve the development of preventative and interventional approaches.